The Major Floral Promoter NtFT5 in Tobacco (Nicotiana tabacum) Is a Promising Target for Crop Improvement - Schmidt, Florentin J.; Zimmermann, Marius M.; Wiedmann, David R.; Lichtenauer, Sophie; Grundmann, Lena; Muth, Jost; Twyman, Richard M.; Prüfer, Dirk; Noll, Gundula A. (Frontiers in Plant Science, 2020)
The FLOWERING LOCUS T (FT)-like gene family encodes key regulators of flower induction that affect the timing of reproduction in many angiosperm species. Agricultural research has therefore focused on such genes to improve the success of breeding programs and enhance agronomic traits. We recently identified a novel FT-like gene (NtFT5) that encodes a day-neutral floral activator in the model tobacco crop Nicotiana tabacum. However, further characterization is necessary to determine its value as a target for breeding programs. We therefore investigated the function of NtFT5 by expression analysis and mutagenesis. Expression analysis revealed that NtFT5 is transcribed in phloem companion cells, as is typical for FT-like genes. However, high levels of NtFT5 mRNA accumulated not only in the leaves but also in the stem. Loss-of-function mutants (generated using CRISPR/Cas9) were unable to switch to reproductive growth under long-day conditions, indicating that NtFT5 is an indispensable major floral activator during long-days. Backcrossing was achieved by grafting the mutant scions onto wild-type rootstock, allowing the restoration of flowering and pollination by a wild-type donor. The resulting heterozygous Ntft5–/NtFT5+ plants flowered with a mean delay of only ~2 days, demonstrating that one functional allele is sufficient for near-normal reproductive timing. However, this minor extension of the vegetative growth phase also conferred beneficial agronomic traits, including a >10% increase in vegetative leaf biomass on the main shoot and the production of more seeds. The agronomic benefits of the heterozygous plants persisted under various abiotic stress conditions, confirming that NtFT5 is a promising target for crop improvement to address the effects of climate change.